For the people : an appraisal comparison of imagined communities in letters to two South African newspapers - Smith, Jade (Rhodes University, Faculty of Humanities, Department of English Language and Linguistics, 2013)
This thesis reports on the bonds that unify imagined communities (Anderson 1983) that are created in 40 letters prominently displayed on the opinions pages of the Daily Sun, a popular tabloid, and The Times, a daily offshoot of the mainstream national Sunday Times. An APPRAISAL analysis of these letters reveals how the imagined communities attempt to align their audiences around distinctive couplings of interpersonal and ideational meaning. Such couplings represent the bonds around which community identities are co-constructed through affiliation and are evidence of the shared feelings that unite the communities of readership. Inferences drawn from this APPRAISAL information allow for a comparison of the natures of the two communities in terms of how they view their agency and group cohesion. Central to the analysis and interpretation of the data is the letters' evaluative prosody, traced in order to determine the polarity of readers' stances over four weeks. Asymmetrical prosodies are construed as pointing to the validity of 'linguistic ventriloquism', a term whose definition is refined and used as a diagnostic for whether the newspapers use their readers' letters to promote their own stances on controversial matters. Principal findings show that both communities affiliate around the value of education, and dissatisfaction with the country's political leaders, however The Times' readers are more individualistic than the Daily Sun's community members, who are concerned with the wellbeing of the group. The analysis highlights limitations to the application of the APPRAISAL framework, the value of subjectivity in the analytical process, and adds a new dimension to South African media studies, as it provides linguistic insights into the construction of imagined communities of newspaper readership.
Keywords: Daily Sun (Johannesburg, -- South Africa); Times (Johannesburg, -- South Africa); Mass media and social integration -- South Africa; Language and languages -- Usage; Mass media and language -- South Africa; Mass media and culture -- South Africa; Belonging (Social psychology)